Historical and Archaeological Perspectives on the Itzas of Petén, Guatemala - Rice, Don S. (Don Stephen); Rice, Prudence M. (Book collections on Project MUSE., 2018)
Historical and Archaeological Perspectives on the Itzas of Peten, Guatemala is the first exhaustively detailed and thorough account of the Itzas--a Maya group that dominated much of the western lowland area of tropical forest, swamps, and grasslands in Peten, Guatemala. Examining archaeological and historical evidence, Prudence Rice and Don Rice present a theoretical perspective on the Itzas' origins and an overview of the social, political, linguistic, and environmental history of the area; explain the Spanish view of the Itzas during the Conquest; and explore the material culture of the Itzas as it has been revealed in recent surveys and excavations. The long but fragmented history of the Peten Itzas requires investigation across multiple periods and regions. Chapters in this six-part overview interweave varying data pertaining to this group--archaeological, artifactual, indigenous textual, Spanish historical--from multiple languages and academic fields, such as anthropology, archaeology, linguistics, ecology, and history. Part I introduces the lowland Itzas, northern and southern, with an emphasis on those of the central Peten lakes area. Part II discusses general Itza origins and identities in the Epiclassic period, while part III reviews Spanish perceptions and misconceptions of the Peten Itzas in their Contact-period writings. With these temporal anchors, parts IV and V present the archaeology and artifacts of the Peten Itzas, including pottery, architecture, and arrow points, from varied sites and excavations but primarily focusing on the island capital of Tayza/Nojpeten. Part VI summarizes key data and themes of the preceding chapters for a new understanding of the Peten Itzas. A companion volume to The Kowoj--a similar treatment of the Peten Itzas' regional neighbors--Historical and Archaeological Perspectives on the Itzas of Peten, Guatemala demonstrates the unique physical, cultural, and social framework that was home to the Peten Itza, along with their backstory in northern Yucatán. Archaeologists, historians, art historians, and geographers who specialize in the Maya and the Postclassic, Contact, and Colonial periods will find this book of particular interest. Contributors: Mark Brenner, Leslie G. Cecil, Charles Andrew Hofling, Nathan J. Meissner, Timothy W. Pugh, Yuko Shiratori